Helminths and Siphonaptera parasites of five species of rodents in localities of the Oriental Basin, Mexico - Falcón-Ordaz, Jorge; Acosta, Roxana; Fernández, Jesús A.; Lira-Guerrero, Georgina (Instituto de Ecología, A.C., 2012)
The Oriental Basin is located in part of the states of Puebla, Tlaxcala and Veracruz, inside of the Trans-Mexican Volcanic Axis; so far, only two helminth species have been recorded (Caballerolecythus ibunami and Lamotheoxyuris ackerti) and three siphonapterans (Anomiopsyllus perotensis, Stenistomera alpina and Echidnophaga gallinacea). Two sampling visits to the area were carried out in June of 2007 and July of 2008, including five localities in the region; eight helminth and nine flea taxa were collected from Liomys irroratus, Dipodomys phillipsii, Peromyscus difficilis, P. maniculatus and Reithrodontomys megalotis. New hosts and localities records for seven helminths and one taxa for fleas were found.